Evolutionary Adaptations to Climate Change in Australian Flora - D’Agui, Haylee Marie (Curtin University, 2017)
Climate changes have been impacting ecosystems worldwide. Southwest Western Australia (SWA) is experiencing increased drought with climate change, causing great concerns for the continuing persistence of its extraordinary plant diversity. The potential of SWA plants to adapt to increased drought through rapid evolution was investigated. Results indicate that the SWA flora has tolerated recent climate changes, with potential for tolerance of further changes; however altered fire regimes may be detrimental to further adaptation and survival.